PENERAPAN ASAS-ASAS HUKUM EKONOMI SYARIAH PADA PERATURAN MENTERI PERDAGANGAN NOMOR 24 TAHUN 2020 TENTANG PENETAPAN HARGA PEMBELIAN PEMERINTAH UNTUK GABAH ATAU BERAS - ayu, mega gustia; Atika, Atika; Himsyah, Fatroyah Asr (Program Studi Muamalah Fakultas Syariah dan Hukum, 2021)
ABSTRACT The Government has issued a policy in the form of Regulation of the Minister of Trade No.24 of 2020 concerning The Determination of Government Purchase Prices for Grain orRice. In this case the government with its authority to set the purchase price of thegovernment (HPP) which aims to maintain food availability and food price stability,especially for the type of staple food rice. The policy on the purchase price of thegovernment for grain or rice is expected to be a reference to provide incentives for ricefarmers by providing guarantees so that prices do not fall during the harvest. Departing from this background, the author is interested in studying more deeplyabout the pricing of grain or rice because one of the problems often experienced by farmersis the fall in the price of grain or rice during the harvest and whether in the determinationof grain or rice HPP has applied the principles of Sharia Economic Law. In this study, the author has used a type of library research that collects materials andinformation from sources available in the library, such as books, magazines, journals,reports, documents, or notes. This research is normative research where the data obtainedand processed is secondary data derived from the source of literature. The data source usedin this study consists of primary legal materials, namely Regulation of the Minister ofTrade No. 24 of 2020 concerning The Determination of Government Purchase Prices forGrain or Rice, secondary legal materials, namely books, articles, and journals related to theprinciples of Sharia Economic Law and government purchase pricing. Meanwhile, tertiarylegal materials are The Great Dictionary of Indonesian, English Dictionary, Encyclopediaof Islamic Law, and so on. The result of this study is the government has applied the principles of ShariaEconomic Law in determining the purchase price of grain or rice, namely the Principle ofGodliness (at-Tauhîd), the Principle of Justice ('Adâlah), the Principle of Ibahâh (Mabda'al-Ibahâh), the Principle of Benefit (al-maslahah), the Principle of Manfaah (TabaManafii), the Principle of Consensualism (Mabda' ar- Radha'iyyah), the Principle ofHelping (Ta'âwun), the Principle of Balance (Mabda' at-Tawazun fi al-Mu'awadah), thePrinciple of Belief (Amânah), Principle of Honesty (Shiddîq), the Principle of Cooperation(Musyarakah), and the Principle of 'Adâmul Gharâr. Keywords: Islamic economic law principles, government purchase price, rice,unhulled rice